Early Evaluation of Renal Function in High-Risk Patients after Off-Pump Coronary Artery Bypass Grafting (Cardiovascular Journal, 2016)
Background: Cardiopulmonary bypass (CPB) is an unphysiological state and widely regarded as an important contributor to renal failure. Despite improvement in cardiopulmonary bypass technique, anesthesia and intensive care, perioperative renal dysfunction still represents a significant and potentially lethal complication after coronary artery bypass graft surgery (CABG). Renal dysfunction is a serious complication of coronary revascularization with CPB and results in increased morbidity, mortality and prolonged hospital stay. We compared the incidence of perioperative renal dysfunction in patients who underwent CABG, on-pump and off-pump (OPCAB) Methods: A total of 60 high -risk patients with ischaemic heart diseases were included in the study who underwent CABG. Out of the total 60 patients, 30 were in the Off-pump group (Group A) and the rest 30 were in the On-pump group (Group B). They were diagnosed as high-risk patients considering serum creatinine level>1.7mg/dl with age ?60 years, ejection fraction 30-40%. Renal function was evaluated in both groups preoperatively and postoperatively (on 1st, 2nd and 7th postoperative day) and compared between two groups.Results: One patient in the On-pump group died on 6th postoperative day. Preoperative renal parameters were also similar and showed no statistically significant difference. So both groups were comparable. Comparison of renal parameter in OPCAB and on-pump CABG between preoperative and 7th day postoperatively found in this study were blood urea 50.33±6.29, 39.87±4.8 vs 52.67±9.05 , 66.21±6.91 ; S. Creatinine (mg/dl) 1.94±0.19 , 1.28±0.19 vs 2.07±0.31 , 2.82±0.47; Creatinine Clearance Rate(ml/min) 46.61±4.1, 71.51±12.3 vs 46.53±4.6, 34.02±4.49 ; Urine output (ml/24 hrs)1692.7±71.53, 1755.7±82.91 vs 1591.2±78.76, 1492.1±196.29 all are statistically significant(p0.05). Statistically significant difference of renal parameters in different postoperative days showed evidence of well preservation of renal function in OPCAB.Conclusion: Adaptation of OPCAB offers better preservation of renal function as well as better early postoperative outcome specially in high-risk CABG patients.Cardiovasc. j. 2016; 9(1): 23-30